Pengaruh Perendaman Obat Kumur Klorheksidin 0,2% Terhadap Kekuatan Tekan Resin Komposit Nanofil - Mintarso, Citra Amaliasari; , drg. Noor Hafida Widyastuti, Sp.KG (2017)
As a dental restorative material, nanofilled composite resin possesses high aestethic and good mechanical properties which makes it a proper restorative material for posterior teeth. One of mechanical properties which can be found in restorative materials is compressive strength. The mechanical properties of composite resin can be affected by chemical solutions such as mouthwash. Chlorhexidine 0,2% is a gold standard antiseptic oral mouthwash. The objective of this research is to examines the effect of chlorhexidine 0,2% mouthwash on compressive strength of nanofilled composite resin. This research used 32 specimens of nanofilled composite resin. The specimen were prepared in cylinder acrylic mold of 4 mm diameter and 8 mm height. Specimens then divided into control group and experimental group with 16 specimens in each group. Specimens in control group were immersed in artificial saliva for 48 hours while the specimens in experimental group were immersed in artificial saliva for 24 hours and then immersed in chlorhexidine 0,2% mouthwash for 24 hours. The compressive strength of each specimens are tested using Universal Testing Machine. The result showed that the average of compressive strength were lower in experimental group. Parametric statistic analysis independent sample t-test of the result indicated a significant gap of compressive strength between control group and experimental group with p=0,000 (p<0,05). It can be concluded that immersion in chlorhexidine 0,2% mouthwash has effect on the compressive strength of nanofilled composite resin.